Contrasting effects of environmental change on the radial growth of co-occurring beech and fir trees across Europe - Bosela, Michal; Lukac, Martin; Castagneri, Daniele; Sedmák, Róbert; Biber, Peter; Carrer, Marco; Konôpka, Bohdan; Nola, Paola; Nagel, Thomas A; Popa, Ionel; Roibu, Catalin Constantin; Svoboda, Miroslav; et al. (The Science of the total environment, 2018)
Under predicted climate change, native silver fir (Abies alba) and European beech (Fagus sylvatica) are the most likely replacement species for the Norway spruce (Picea abies) monocultures planted across large parts of continental Europe. Our current understanding of the adaptation potential of fir-beech mixed forests to climate change is limited because long-term responses of the two species to environmental changes have not yet been comprehensively quantified. We compiled and analysed tree-ring width (TRW) series from 2855 dominant, co-dominant, sub-dominant and suppressed fir and beech trees sampled in 17 managed and unmanaged mixed beech-fir forest sites across Continental Europe, including Bosnia and Herzegovina, Germany, Italy, Romania and Slovakia. Dendroecological techniques that combine various detrending methods were used to investigate variation in radial growth of co-occurring fir and beech trees. Coincidental with peak SO2 emissions, the growth of silver fir declined between 1950 and 1980 at most sites, whereas beech growth increased during this period. Correspondent to a significant warming trend from 1990-2010, average beech growth declined, but silver fir growth increased. Long-term growth patterns and growth-climate sensitivity of fir and beech trees did not significantly differ between managed and unmanaged forests. Multi-decadal changes in the growth rate of all vertical tree classes were similar. In contrast to previous indications of limited drought susceptibility of beech mixed stands, this study suggests that the mixture of tree species in forest stands does not necessarily prevent growth depressions induced by long-term environmental change. Our results further imply that forest management does not necessarily alter their sensitivity to environmental changes.
Keywords: Tree rings; Plant–climate interactions; Trees; Abies; Growth sensitivity; Bosna a Hercegovina; stromy; Environmental Monitoring; Itálie; Mixed forests; Norway; Germany; Rumunsko; Slovakia; Slovenská republika; jedle; klimatické změny; Německo; monitorování životního prostředí; Climate Change; Romania; Dendroecology; buk (rod); Bosnia and Herzegovina; Climate change; Italy; Norsko; Fagus